Enterprise architecture model: an approach proposition. A case study of information systems in the hospitality industry - Serdeira Azevedo, Paula (2013)
This paper discusses the role of enterprise architecture representation, in the context of ERP (Enterprise Resource Planning) information systems, as an instrument for an organization to reflect on itself and develop its business strategies and respective alignment with Information Systems. The paper proposes a representation model of enterprise architecture, as a tool for recommending good practices, and it emerges from a case study undertaken in the context of and investigation on advantages and limitations of ERP systems in the hospitality industry. The proposed approach is also inspired on other academic or market propositions suitable for the objectives of the investigation. It consists on a set of items representing the steps that must be taken by top managers and IS managers.